A green method of preparing a natural and degradable wound dressing containing aloe vera as an active ingredient. (1st October 2021) - Wang, Yilei; Zhang, Yingbing; Lin, Zhuangsheng; Huang, Ting; Li, Wen; Gong, Wanxin; Guo, Yuhui; Su, Jianmin; Wang, Jinyi; Tu, Qin
Abstract: Past commercial and clinical research on wound dressings generally only focused on their therapeutic activities, however, how to make products environmentally friendly with reduced production of hazardous waste while ensuring product functionality is becoming a crucial and burning issue in the manufacturing industry. To address this problem, we developed a natural, degradable and environmentally friendly hydrogel wound dressing using aloe vera (AV) as an active ingredient. The hydrogel wound dressing was prepared using all natural ingredients, comprised of sodium hyaluronate (SH), dopamine (DA), chitosan (CS), and AV, and using a green natural deep eutectic solvent (DES) as a green solvent. The resultant DES-SH-CS/DA/AV hydrogel was easy to degrade and the preparation process was environmentally friendly. The chemical and physical properties of the hydrogel samples were characterized. The DES-SH-CS/DA/AV hydrogel showed good cytocompatibility tested using NIH-3T3 fibroblast cells, and antibacterial properties against both gram-positive ( S. aureus ) and gram-negative ( E. coli ). Furthermore, the hydrogel promoted skin tissue regeneration healed the wound of mouse skin after surgery within 12 days. The H&E staining was used to assess the integrity of the regenerated epidermis and dermis and the new generation of skin attachments in this work. Overall, our study showed the DES-SH-CS/DA/AV hydrogel we developed has the potential to be used as a natural and green wound dressing.